Valproic Acid-Induced Hair Curling - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
A 47-year-old white female patient treated with valproic acid (VPA) 500mg 3xd, at Utrecht University, the Netherlands, developed curling of the hair which gradually resolved over 5 years continuous therapy, with blood levels ranging from 97 to 146 mg/L.